Effect of Equal-channel angular pressing on mechanical Properties: An overview. (2021) - Gupta, Akash; Chandrasekhar, Balla; Saxena, Kuldeep K.
Abstract: Equal-channel angular pressing (ECAP) is also known as Equal-channel angular extrusion (ECAE) process. ECAP is a Severe plastic deformation process which can produce ultrafine grains with superior mechanical properties. There is a very significant role of number of passes in the ECAP process, mechanical properties and grain refining is depending on it. This study is focused on the influence of the number of passes and processing routes on hardness, tensile strength and elongation of different alloys, so only mechanical properties are mentioned under this review. Among all the processing route of the ECAP process, BC route shows the maximum strength. Some limitations or disadvantages related to the ECAP process are also discussed in this study.